Kajian Miskonsepsi Mahasiswa Tentang Metabolisme: Studi pada Mata Kuliah Biokimia - Laili, Shofia Izzatul; Sari, Ela Puspita; Aisya, Zulfiana Rihhadatul; Childa, Qorri Aina; Saputri, Rifda Ayu; Prasetyo, Dody Rahayu (Jurnal Pendidikan Ilmu Pengetahuan Alam (JP-IPA), 2025)
This study aims to identify student misconceptions related to the concept of metabolism in biochemistry. The method used is a descriptive quantitative approach with a three-tier diagnostic test approach: answer choices, reasons, and level of confidence. The research subjects were students who have taken or are currently taking biochemistry. The main instrument was a three-tier diagnostic test. Data were collected through in-person and online test distribution. The data analysis technique used a combination of the three tiers to determine misconception patterns. Then, the three questions with the highest level of misconceptions were analyzed to find the causes of misconceptions. The classification of answer combinations in the three-tier diagnostic test was determined based on the results of answers at all levels. The results indicated that misconceptions were still found in several important concepts, such as the role of oxygen in cellular respiration and the comparison of energy produced by macronutrients. Some students believed that oxygen plays a direct role in preventing glucose or that carbohydrates produce the most energy simply because they are the main energy source.